Physical, structural and optical properties of willemite derived from white rice husk ash doped with manganese dioxide - Al-Nidawi, Ali Jabbar Abed (2017)
Over the last few years, the manganese doped willemite (Zn2SiO4) draw much attention in the solid state lasers, phosphors, lighting and optical devices. Intensive research has been carried out to use pure SiO2 and not much work had been done on used waste solid materials for synthesis Zn2SiO4:Mn2+ and little of them used SiO2 derived from white rice husk ash. The purpose of the current study is to produce the willemite derived from white rice husk ash and enhancement of their properties by MnO2 doping, which expected to reduce the cost of electroluminescence devices. Thus, in this study, willemite glass-ceramic and MnO2 doped willemite were synthesised from white rice husk ash as a source of silicon, ZnO and MnO2using the conventional solid-state method. The current study involves an investigation of the effect of sintering temperature and Mn-dopant concentration on the physical, structure and optical properties of willemite. This study indicates that the average density and linear shrinkage of MnO2-willemite increased with increasing of concentration of MnO2 dopant and sintering temperature. The result of x-ray diffraction revealed that the amorphous phase at un-sintered, 500, 600, and 700 °C respectively, metastable phase β-Zn2SiO4 at 800 °C changed to stable phase α-Zn2SiO4 at 900 and 1000 °C. The FESEM micrographs of Zn2SiO4:Mn2+ showed at lower sintering temperature 500, 600 and 700 °C the morphology showed that the grains are still in irregular shape and aggregated. After 800 °C the microstructure of sample started to change which is the sharper edge of the glass microstructure start to decrease cause of the softening effect. Therefore, at 900 and 1000 °C the morphology of the willemite glass-ceramic became granular due to product the crystal in the sample. The FTIR result suggested that the formation of willemite crystal phase based on the presence SiO2 and ZnO4 bands. The result from UV-VIS spectroscopy indicate that the optical band gap for glass and glass-ceramic sample decreased as the concentration of dopant and sintering temperature increased. The emission intensity of all Zn2SiO4 sample exhibited a strong green luminescence at 530 nm which due to transition of unshielded 3d5electrons of Mn ion from the first excited state of 4T1(4G) to the ground state of 6A1(6S). The emission intensity of glass and glass-ceramic sample increased with the increased of the MnO2 concentration and the highest intensity of it at 5 wt.% doping.